FROM NORMATIVE IDEALS TO ACADEMIC SYSTEMS: STRENGTHENING PROPHETIC VALUES IN POSTGRADUATE GRADUATE PROFILES - Mokhammad Samson Fajar; Heri Cahyono (AT-TAJDID, 2026)
The increasing technocratic orientation of postgraduate education has raised concerns about the marginalization of ethical responsibility and character formation in advanced scholarship. This study aims to develop a systemic framework for strengthening prophetic values within the postgraduate graduate profile of Universitas Muhammadiyah Metro. Using a qualitative conceptual–normative design, the study synthesizes Islamic educational philosophy, contemporary literature on graduate attributes, higher education policy documents, and institutional practices. The analytical process is guided by the Data Information Knowledge Wisdom framework to translate normative values into operational academic strategies. The results demonstrate that prophetic values can be positioned as the core of the postgraduate graduate profile, integrating academic competence, research capability, professional responsibility, and moral–spiritual orientation. Four prophetic dimensions integrity, trustworthiness, communicative responsibility, and wise intelligence are shown to align systematically with teaching, research, and community engagement. The study further proposes a nine-stage institutional roadmap encompassing paradigm alignment, methodological internalization, human resource development, curriculum and learning outcome integration, cultural and architectural reinforcement, cross-disciplinary knowledge integration, sustained value campaigning, and reflective evaluation. Collectively, these stages illustrate how prophetic values transition from normative ideals to institutional practice. The findings suggest that prophetic values must move from slogan to system in order to meaningfully shape postgraduate outcomes. By offering a DIKW-based institutional roadmap, this study contributes a replicable conceptual model for Islamic higher education institutions seeking to balance academic excellence with integrity, responsibility, and public benefit. The framework has implications for policy development, quality assurance, and future empirical research on value-based postgraduate education.